Group Mindfulness-Integrated Cognitive Behavior Therapy (MiCBT) Reduces Depression and Anxiety and Improves Flourishing in a Transdiagnostic Primary Care Sample Compared to Treatment-as-Usual: A Randomized Controlled Trial - Francis, Sarah E. B.; Shawyer, Frances; Cayoun, Bruno; Enticott, Joanne; Meadows, Graham N. (Frontiers in Psychiatry, 2022)
Objectives: This study investigated the effectiveness of a group-based eight-week intervention, Mindfulness-integrated Cognitive Behavior Therapy (MiCBT), to decrease psychological distress and increase well-being in a heterogeneous population in primary health care. MiCBT focuses on the importance of interoception and its interaction with cognition in emotional experience. These interactions are represented in the co-emergence model of reinforcement, in which non-reactivity (equanimity) to interoceptive signals facilitates adaptive behavior. Methods: Participants (n = 125, aged 20-72) were randomized to two groups (MiCBT), and treatment as usual (TAU). Outcomes were assessed at pre-, mid- and post-intervention and at 6-month follow-up. The primary outcome was psychological distress, measured by the Depression, Anxiety and Stress Scale (DASS-21). Secondary outcome measures were the Kessler Psychological Distress Scale-10 (K10), Satisfaction with Life Scale (SWLS), and Flourishing Scale (FS). Mediator or process measures of interoceptive awareness, metacognitive awareness (decentering), equanimity, and social functioning were included to investigate putative mediators. Results: The MiCBT intervention significantly reduced DASS-21 scores at mid and post-treatment and the gains were maintained at 6-month follow-up (p < .0001, d = .38). Flourishing scores also showed significant improvement post treatment and at 6-month follow-up (d =.24, p <.0001). All measures selected showed a similar pattern of positive change, with the exception of the SWLS, which failed to reach significance. Mediation analysis suggested equanimity to be the most influential mediator of the primary outcome. Conclusions: The results support the effectiveness of MiCBT in creating rapid and sustainable reduction of psychological distress and improvement in flourishing in a primary mental health care setting with heterogenous groups. These promising results support the scaled-up implementation of this intervention.